Analyzing farm household strategies for food security and climate resilience: The case of Climate-Smart Villages of Southeast Asia - Ferrer, Alice J.; Yen, Bui Tan; Kura, Yumiko; Minh, Ngo Duc; Pavelic, Paul; Amjath-Babu, Tharayil Shereef; Sebastian, Leocadio S. (2018)
This paper develops a conceptual framework with an indicator-based approach to assess Climate-Smart Villages (CSVs) and applies it to case study sites in Lao PDR (Ekxang CSV), Cambodia (Rohal Suong CSV), and Vietnam (Tra Hat CSV) in Southeast Asia. The intensification, extensification, diversification, commercialization, alteration of practices, use of common lands, migration strategies that can augment climate resilience, farm income, assets, and food security are assessed based on a composite index of the strategies and key outcome variables. The study demonstrates a method that can be applied widely for assessing climate-smart agriculture strategies and finding possible entry points for climate-smart interventions. The influence of gender in resource control and livelihood strategies is also discussed. It is also evident that the climate-smart interventions can augment different livelihood strategies of farmers and enhance the developmental and climate resilience outcomes. There is a need to prioritize the possible interventions in each case and implement them with the help of donor agencies, local institutions, and government offices.